Evaluation of thermophysical properties of imidazolium-based phenolate ionic liquids - Shah, S.N. (American Chemical Society, 2015)
Thermophysical properties of imidazolium-based phenolate ionic liquids (ILs) were investigated over a wide temperature range. Different alkyl groups such as ethyl, butyl, hexyl, octyl, and decyl were tethered to the 1-methylimidazolium cation to study the effect of alkyl chain length on thermophysical properties such as density, viscosity, refractive index, heat capacity, and surface tension. The thermal stability of the phenolate ILs was investigated using thermogravimetric analysis. From the experimental values of density and surface tension, the molecular volume, standard molar entropy, lattice energy, surface entropy, and surface enthalpy of the ILs were calculated at 303.15 K. Â© 2015 American Chemical Society.